(untitled) (Research, Society and Development, 2022)
Commiphora leptophloeos (Burseraceae) is a plant belonging to the genus Commiphora popularly known as imburana or umburana. It found in the caatinga and cerrado of Brazil. The species belonging to the genus Commiphora are used in folk medicine as anti-inflammatory, antimicrobial and in the treatment of several diseases. In recent decades, cases of diseases caused by the Aedes aegypti mosquito have increased considerably, making it necessary to seek alternative measures to combat the vector. The present study aimed to analyze, through bibliographic review, Commiphora leptophloeos regarding aspects of family, genus and species; and describe the relationship of this species with Aedes aegypti, highlighting natural products in the control. The findings indicate repellent activity of species of the genus Commiphora on insects, in addition to the presence of some mono and sesquiterpenes compounds, widely distributed in the genus, among them α-pinene, camphene and β-pinene. Studies also confirm the ethnobotanical uses of C. leptophloeos, as well as its potential in the treatment of diseases. The analyzed literature indicates the antimicrobial activity of the aqueous extract of the bark and stem of C. leptophloeos against Staphylococcus epidermidis. Other data reveal that the essential oil of this species has larvicidal and deterrent activity against A. aegypti. The revised literature suggests the importance of natural products, their advantages as biopesticides, as well as the effectiveness of C. leptophloeos in combating the A. aegypti mosquito, stressing the need for further studies and tests to isolate the compounds present in this species.